Modern applications of profit-sale (Bayʿ murābaḥah) from a Maqāsid Sharīʿah perspective - Ali, Mohammed Farid; Mohd Yunus, Saidatolakma (IIUM Press, International Islamic University Malaysia, 2019)
This paper looks into profit-sale (murābaḥah), a nominal sale contract in Islam, in search for Shari'ah objectives embedded in the corpus and in the terms and conditions of the contract. In light of these objectives, applications of the profit-sale contract as a financing tool by the Islamic Finance Institutions (IFIs) are examined. The study discovers that some modern applications bypass the primary Shari'ah objectives of a sale contract, such as the seller taking liability of possible risks and having real possession of the items on sale. Contrary to this, the seller transfers his liability to the customer, and takes possession (qabḍ) of the goods on paper only, instead of possession in the real sense. Such applications distort the mode of trading real goods into a mere disguise for an increase on credit or riba.